Informal Reading Inventory of the Grade 2 Pupils in Talisay Elementary School - Villaruel, Princess (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the reading abilities of Grade 2 pupils of Talisay Elementary School using the Informal Reading Inventory. It was anchored on Reading Development Theory, Constructivist Learning Theory, and Sociocultural Theory, which supported the assessment of pupils’ reading development, meaning making, and need for guided support. The study used a descriptive research design and total population sampling involving 24 Grade 2 pupils. A 35-word oral reading passage was used to assess gender profile, reading speed and rate, word recognition and reading accuracy, and reading comprehension based on PHIL-IRI scores. Results showed that 14 respondents were female and 10 were male. Female pupils had a higher average reading rate of 93.5 words per minute compared with 80.6 words per minute among male pupils. In word recognition and reading accuracy, 6 pupils were at the independent level, 3 were at the instructional level, and 15 were at the frustration level. Female pupils also recorded higher average word recognition and accuracy scores than male pupils, although both groups were classified at the frustration level. In reading comprehension, 10 pupils were independent, 9 were instructional, and 5 were at the frustration level. The study concluded that pupils had varied reading abilities, with stronger comprehension performance but weaker word recognition and accuracy. It recommended differentiated reading instruction, regular Informal Reading Inventory administration, guided oral reading, repeated reading, phonics drills, sight-word practice, comprehension activities, parental support, and contextualized literacy interventions. The study supports SDG 4 on Quality Education and SDG 5 on Gender Equality by promoting early literacy assessment and equitable learner support. Its sustainability impact lies in strengthening educational, institutional, community, and socio-economic sustainability through data-based reading intervention and improved foundational literacy.
Keywords: Comprehension; Informal Reading Inventory; PHIL-IRI; Reading Accuracy; Reading Intervention; Reading Rate; Reading Speed; Word Recognition